Spatial Distribution of Heavy Metal Contamination in Road Dust Samples from an Urban Environment in Samsun, Türkiye - Istanbullu, Seyma Nur; Sevik, Hakan; Isinkaralar, Kaan; Isinkaralar, Oznur (Springer Science and Business Media LLC, 2023)
Road dust is an environmental pollution indicator created by human activities for urban land use. This study aimed to determine the spatial distribution pattern and degree of trace metals in road dust samples collected from 5 different areas in Samsun city center. The trace metals of Mn, Co, Cd, Cr, Cu, Ni, Pb, and Zn are the most examined contaminants in road dust because their hot-spot areas were mainly associated with high traffic density. Factors governing potential contamination index range values of Co, Cr, and Ni were 0.34-0.62, 0.23-0.78, and 0.24-0.48 as the lowest contamination. However, potential contamination index values of Cu, Pb, and Zn in the main road site were 1.80, 2.32, and 2.84 suggesting that relatively high values were uncontaminated to moderately. Pollution assessment methods were applied to toxic metals and revealed that Samsun city had been affected as uncontaminated to moderately contaminated by anthropogenic emission of heavy metals.
Keywords: China; Lead; Metals, Heavy; Humans; Dust; Cities; Environmental Pollution; Risk Assessment; Environmental Monitoring; Trace Elements; 13. Climate action; 11. Sustainability; 6. Clean water